The Dynamics of Ethnonationalism and Conflict Resolution in Papua (MUHARRIK: Jurnal Dakwah dan Sosial, 2021)
The dynamics of the conflict in Papua which is often volatile and take a long way are the impact of the complexity of the problem since it was integrated with the Unitary State of the Republic of Indonesia. Differences in perspective from the history of integration, discrimination, economic inequality, and human rights violations encourage indigenous Papuans to give birth to an ethnonationalism movement. On the other hand, the dual strategic approach that has been implemented in Papua is both in welfare and security. The Government seeks to improve and facilitate access to the fundamental rights of the Papuan people within the framework of development in line with local wisdom or known as ethno-development. In order to contribute to previous studies, this article attempts to critically analyze the ethnonationalism movement in Papua and the factors that drive the emergence of conflicts and strategic efforts to resolve conflicts through ethnodevelopment. The ethnodevelopment approach is based on the cultural integrity of the local population who play an essential role in actively participating in social change. Ethno-development is also a parameter for the implementation of space for freedom of expression in Papua to acknowledge local culture and wisdom.